2021
DOI: 10.1021/acs.jproteome.1c00443
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Click Chemistry Tag for Universal Proteome Sample Preparation for Top-Down and Bottom-Up Analysis

Abstract: Successful proteome analysis requires reliable sample preparation beginning with protein solubilization and ending with a sample free of contaminants, ready for downstream analysis. Most proteome sample preparation technologies utilize precipitation or filter-based separation, both of which have significant disadvantages. None of the current technologies are able to prepare both intact proteins or digested peptides. Here, we introduce a reversible protein tag, ProMTag, that enables whole proteome capture, clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…A protein solution containing sodium dodecyl sulphate (SDS) and dithiothreitol (DTT) was loaded into filtering columns and washed exhaustively with 8 M urea in HEPES buffer. Proteins were then incubated overnight with trypsin sequencing grade (Promega, Madison, USA) after reduction with DTT and alkylation with iodoacetamide (IAA) [ 25 ]. The digested peptides (supernatant) were collected by centrifuging for 20 min at 14,000 rpm at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A protein solution containing sodium dodecyl sulphate (SDS) and dithiothreitol (DTT) was loaded into filtering columns and washed exhaustively with 8 M urea in HEPES buffer. Proteins were then incubated overnight with trypsin sequencing grade (Promega, Madison, USA) after reduction with DTT and alkylation with iodoacetamide (IAA) [ 25 ]. The digested peptides (supernatant) were collected by centrifuging for 20 min at 14,000 rpm at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Tetrazine ligation has emerged as a powerful bioorthogonal labeling reaction that is distinguished for its speed, selectivity, and tolerance of a wide range of functional groups. Among their numerous applications in chemical biology, tetrazines have been used as bioorthogonal handles in proteomic workflows. Recently, the Carrillo group has demonstrated that 3,6-dialkylthiotetrazines can undergo dynamic nucleophilic substitution reactions and that post-functionalization through Diels–Alder reaction with norbornene gives dihydropyridazine products that no longer exchange. , Applications to the syntheses of macrocycles, macromolecular cages, and to polymer chemistry were described, but applications in biology had not been reported . Recently, our group has described a method for preparing thiomethyltetrazines via a one-pot reaction between carboxylic esters and methylthiocarbohydrazide iodide .…”
Section: Introductionmentioning
confidence: 99%
“…Glycomics investigations commonly rely on sophisticated techniques such as hydrophilic interaction chromatography (HILIC), polymeric anion exchange (WAX), and porous graphitic carbon (PGC) to purify complex glycans [ 4 , 5 ] and mass spectrometry (MS) [ 6 ] to detect desired glycan-containing fractions, and it is further challenging to perform chemical modifications of the selected glycans to facilitate biological studies [ 7 ]. In contrast, the field of proteomics has brought about innovative [ 8 ], selective, mild [ 9 ], and occasionally reversible modifications [ 10 ] of proteins enabling site-specific tagging [ 11 ] and pull-down approaches [ 12 ]. Therefore, the field of proteomics has rapidly progressed with assigning structures and functions to an ever-increasing number of targets [ 13 ].…”
Section: Introductionmentioning
confidence: 99%